DETERMINASI FAKTOR PENENTU KEPUTUSAN PEMBELIAN (STUDI EMPIRIK PADA PRODUK AQUA) - Kiran P Hermandasani, Tumpal J.R. Sitinjak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
The rapid growth of bottled drinking water industry, along with the emergence of various brands of bottled drinking water products circulating throughout Indonesia, has resulted in increasingly fierce competition among producers, making AQUA demanded to survive. One way to maintain and even increase market share is by offering appropriate prices, quality products and good promotions so that they can achieve the desired goal of making consumers take purchasing decisions which are expected to have a positive impact on the company.The theory used to support this writing is the definition of price, product quality, promotion and purchasing decisions, which are used as supporting material for this research.The object of this research is AQUA brand bottled drinking water. The population of this research is AQUA consumers in the Jakarta area in 2018, where the sampling technique is non-probability sampling by using judgmental sampling, with a sample size of 100. Data collection is done by communication techniques where questionnaires are distributed to 100 respondents. Data analysis techniques used were validity, reliability, descriptive analysis, and multiple regression analysis.The results of data analysis show that prices do not have a positive effect on purchasing decisions. While product quality and promotion have a positive effect on purchasing decisions. This shows that if the quality of the product and promotion is increasing its performance will be followed by a higher purchase decision on the product.Based on the results of the analysis, it can be concluded that product quality and promotion have a positive effect on purchasing decisions. Keywords : Purchasing decisions, Price suitability, Quality of product, Promotion